POLITIK HUKUM DIUNDANGKANNYA QANUN NOMOR 11 TAHUN 2018 TENTANG LEMBAGA KEUANGAN SYARI’AH (LKS) DI PROVINSI ACEH - Rachmatika Lestari; Eza Aulia; Dara Quthni Effida (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2021)
In the section weighing Qanun Aceh Number 11 of 2018 on Islamic Financial Institutions (LKS) states that the juridical reason of the establishment of Qanun LKS is a follow-up to the implementation of Article 21 Qanun Aceh Number 8 of 2014 on the Principals of Islamic Shari'ah. After the promulging of Qanun LKS, many Conventional Bank Financial Institutions in Aceh decided to close their business in Aceh, so that if people still want to use conventional bank services, then the transaction must be done outside Aceh. In fact, almost all business actors in Aceh's economic activities are connected to outside areas, while in outside areas many business actors, especially corporations, have not fully used the Shari'ah banking system. The formulation of the problems discussed in this study is: "Is the legal politics promulgated Qanun Aceh Number 11 of 2018 on Islamic Financial Institutions has been able to improve the economy in Aceh?". The research method used in this research is normative-empirical research on the implementation of normative law provisions (laws) in action on any particular legal event that occurs in a society with a Live Case Study approach, which is an approach to a legal event whose process is still ongoing or has not ended. The results showed that in practice Aceh's economic independence is still very low, in the case of business actors, many obstacles are experienced in the services of Islamic banks, including difficulty making transactions with partners from outside Aceh who generally use conventional bank accounts. The advice given in this study is that conventional financial institutions that have been established in Aceh in facilitating the transactions of business people in Aceh and to succeed financial institutions based on islamic sharia principles only need to open Sharia business units from their conventional financial institutions that have been formed, this is in accordance with the mandate of Article 21 Qanun Aceh Number 8 of 2014 on The Principals of Islamic Shari'ah which is the basis or juridical reason of the establishment of Qanun LKS so that for business actors who transact with business actors outside Aceh who predominantly have not used shari'ah financial institutions can be facilitated in conducting business transactions, so that this will have an final impact on improving the economy in Aceh.